Cost‐effectiveness of home blood pressure telemonitoring and case management in the secondary prevention of cerebrovascular disease in Canada. Issue 2 (20th December 2018) - Padwal, Raj S.; So, Helen; Wood, Peter W.; Mcalister, Finlay A.; Siddiqui, Muzaffar; Norris, Colleen M.; Jeerakathil, Tom; Stone, James; Valaire, Shelley; Mann, Balraj; Boulanger, Pierre; Klarenbach, Scott W.
Abstract : Home blood pressure (BP) telemonitoring and pharmacist case management reduce BP, but cost‐effectiveness assessments are mixed. We examined the incremental cost‐effectiveness of this intervention vs usual care in Canadians with cerebrovascular disease. A Markov decision model cost‐utility analysis examining community‐residing, high‐risk patients with a recent nondisabling cerebrovascular event was created. A lifetime time horizon and health care payer perspective were used. Achieved BP, future cardiovascular risks, and attendant consequences on quality‐adjusted life years and Canadian dollar costs were modeled. BP telemonitoring was assumed to occur for 3 months, then quarterly. Life tables were used to determine overall mortality, adjusted by cardiovascular disease mortality. Relative efficacies of intervention‐associated BP lowering, resource use, and costs were obtained from Canadian published literature. Reduction in systolic BP of 9.7 mmHg was used in the base case; subsequently, robust sensitivity analyses were conducted. The results showed that, over the lifetime horizon, telemonitoring with case management led to net health care savings of $1929 Canadian and increased per‐patient QALYs by 0.83. These findings were robust to sensitivity analysis, with the intervention remaining dominant or highly cost‐effective. Increasing telemonitoring costs by 50% still resulted in the intervention being dominant; if the costs of telemonitoring plus case management were 2‐3 times base case cost, incremental cost‐effectiveness was $1200‐$4700 per quality‐adjusted life year gained. In conclusion, home BP telemonitoring and pharmacist case management poststroke lowered costs and improved QALYs. Strategies and funding for broad implementation of this dominant strategy should be implemented.